Evaluating Students' Perceptions of the Authentic Assessment in An Online English for Specific Purposes Course: A Mixed-Method Approach - Ni Made Anggi Arlina Putri; Wayan Suana; Nurul Aini; Thanakorn Choosukhserm (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2026)
This study investigates Information Technology Education (ITE) students' perceptions of authentic assessments in an online English for Specific Purposes (ESP)  course. As ESP increasingly adapts to online learning environments, traditional testing methods often fall short in assessing practical language skills crucial for professional contexts. Using a mixed-methods approach, the study examines three dimensions of student perception: benefits, advantages, and challenges. Data were collected through a survey administered to 48 students and semi-structured interviews with 9 participants. From the quantitative finding, it revealed that students have a positive attitude toward authentic assessments, particularly valuing their benefit and advantages in some tasks namely presentations, conversation with foreigners, and reading comprehension of information technology-related scientific articles. Moreover, qualitative data suggests that these authentic assessments boost learners’ motivation, confidence, and language proficiency while preparing them for real-world professional environments. However, the data also reported that students faced challenges related to time management, increased workload, technical demands, and also internet connectivity issues. This study highlights the significance of integrating authentic assessment into ESP courses to align language education with contextual and practical needs. It also recommends offering technical support and adopting flexible timelines to address these challenges. This finding offers valuable insights for ESP curriculum development and encourage further study to explore long-term impact of authentic assessment on career readiness.